Blended Learning as a Pedagogical Catalyst for Enhancing University Students’ Writing Skills: A Comparative Study - Mekonnen, Agmasie Tarekegn; Banteyerga Amaha, Hailom (Universitas Jambi, Magister Program of English Education Department, 2026)
This study examined the effectiveness of blended learning in improving academic writing skills among first-year university students at Addis Ababa University, Sefere Selam Health Science College. A quasi-experimental, non-randomized pretest–posttest design was used with 80 students. The control group received conventional face-to-face instruction, while the experimental group learned through blended learning using Telegram and digital feedback tools for writing practice, peer review, and instructor feedback. Writing performance was assessed across six components, and qualitative interviews were used to explore students’ learning experiences. Both groups improved in writing performance; however, the blended learning group showed significantly greater gains, with mean scores increasing from 43.21% to 62.37%. The intervention produced a very large effect size (Cohen’s d = 2.47), indicating strong practical significance. The greatest improvement was seen in grammar and mechanics, suggesting that digital feedback and repeated revision opportunities supported writing development. This study provides empirical evidence from Ethiopian higher education by linking the national Digital Education Strategy (2023) with classroom practice. Guided by the Complex Adaptive Blended Learning System (CABLS) framework, it highlights the pedagogical value of blended learning for improving academic writing in resource-constrained contexts. Academic writing skills; blended learning; higher education; Ethiopia; writing proficiency; digital feedback; Telegram-based learning; EFL writing; quasi-experimental study; instructional technology; peer feedback; writing assessment.